2014
DOI: 10.1111/1755-0998.12244
|View full text |Cite
|
Sign up to set email alerts
|

Application of the LUminometric Methylation Assay to ecological species: tissue quality requirements and a survey of DNA methylation levels in animals

Abstract: The LUminometric Methylation Assay (LUMA) measures global DNA methylation. LUMA depends on digestion of DNA with methyl-sensitive and methyl-insensitive restriction enzymes, followed by pyrosequencing. Until recently, LUMA has been principally used for biomedical research. Here, we use chickens as a model to investigate sample quality issues relating to LUMA and then apply the method to ecological species. First, we assessed the effect of tissue storage conditions on DNA methylation values. This is an importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 24 publications
3
21
0
Order By: Relevance
“…Global methylation quantified by LUMA for dogs appears to be consistent with recent work published by Head et al, which suggests that mammals have intermediate global methylation (Head et al 2014). This publication found that fish had higher global methylation relative to mammals, while birds had lower.…”
Section: Discussionsupporting
confidence: 89%
“…Global methylation quantified by LUMA for dogs appears to be consistent with recent work published by Head et al, which suggests that mammals have intermediate global methylation (Head et al 2014). This publication found that fish had higher global methylation relative to mammals, while birds had lower.…”
Section: Discussionsupporting
confidence: 89%
“…When the methylation levels of these samples were calculated using standard LUMA, it was found that the Hpa II/ Msp I ratios were higher in the more fragmented samplethis is similar to findings reported previously (9, 10). In addition, the methylcytosine levels of these samples were measured using HPLC in order to control for methylation changes.…”
supporting
confidence: 88%
“…Our study also has clear limitations. First, we used the LUMA assay, which is a reliable and a particularly attractive option for wild animals lacking well‐curated genomes (Head, Mittal, & Basu, ). However, the CCGG sites targeted by this assay represent a single composite average of genomic DNA methylation and do not provide any information on finer resolution differences in DNA methylation that may be relevant to environmental risk factors and/or phenotypes.…”
Section: Discussionmentioning
confidence: 99%